Acid suppression therapy, gastrointestinal bleeding and infection in acute pancreatitis: an international cohort study - Demcsák, Alexandra; Soós, Alexandra; Kincses, Lilla; Capunge, Ines; Minkov, Georgi; Kovacheva-Slavova, Mila; Nakov, Radislav; Wu, Dong; Huang, Wei; Xia, Qing; Deng, Lihui; Hollenbach, Marcus; et al. (Pancreatology, 2020)
Background - Acid suppressing drugs (ASD) are generally used in acute pancreatitis (AP); however, large cohorts are not available to understand their efficiency and safety. Therefore, our aims were to evaluate the association between the administration of ASDs, the outcome of AP, the frequency of gastrointestinal (GI) bleeding and GI infection in patients with AP. - Methods - We initiated an international survey and performed retrospective data analysis on AP patients hospitalized between January 2013 and December 2018. - Results - Data of 17,422 adult patients with AP were collected from 59 centers of 23 countries. We found that 23.3% of patients received ASDs before and 86.6% during the course of AP. ASDs were prescribed to 57.6% of patients at discharge. ASD administration was associated with more severe AP and higher mortality. GI bleeding was reported in 4.7% of patients, and it was associated with pancreatitis severity, mortality and ASD therapy. Stool culture test was performed in 6.3% of the patients with 28.4% positive results. Clostridium difficile was the cause of GI infection in 60.5% of cases. Among the patients with GI infections, 28.9% received ASDs, whereas 24.1% were without any acid suppression treatment. GI infection was associated with more severe pancreatitis and higher mortality. - Conclusions - Although ASD therapy is widely used, it is unlikely to have beneficial effects either on the outcome of AP or on the prevention of GI bleeding during AP. Therefore, ASD therapy should be substantially decreased in the therapeutic management of AP.